Use of a simple in vitro fatigue test to assess materials used in the surgical treatment of stress urinary incontinence and pelvic organ prolapse - Roman, Sabiniano; Mangir, Naside; Hympanova, Lucie; Chapple, Christopher R; Deprest, Jan; MacNeil, Sheila (Neurourology and urodynamics, 2019)
AIMS: Stress urinary incontinence and pelvic organ prolapse are very common conditions with a proportion of patients requiring implantation of synthetic materials for a durable repair. However increasing numbers of post-surgical complications have been reported related to the use of polypropylene meshes. One hypothesis for the adverse response is poor mechanical matching of the relatively stiff polypropylene mesh particularly as materials in the pelvic floor will need to cope with decades of distension as occurs with increase of intraabdominal pressure on coughing, laughing, or sneezing. METHODS: In this study we have undertaken a very simple fatigue testing regime to compare the mechanical abilities of six materials. Four commercial meshes in clinical use and two novel electrospun materials not yet evaluated in the clinic were assessed using a uniaxial tensile test. This was performed on six samples of each dry material and on another six samples of each material after just 3 days of fatigue conditions using a dynamic bioreactor. RESULTS: The four commercial materials showed permanent mechanical deformation after just 3 days of stretching these materials by 25% elongation on a regular dynamic cycle, whereas the two new materials presented more elastic properties without deformation. CONCLUSIONS: We suggest that a test as simple as this 3-day fatigue testing is sufficient to distinguish between materials which have already been found to cause complications clinically and newer materials yet to be tested clinically which will hopefully prove more mechanically appropriate for implantation in the pelvic floor.
Keywords: fatigue test; polypropylene mesh; Tensile Strength; pánevní dno; Mechanical Phenomena; polypropyleny; pelvic floor repair; Polypropylenes; Pelvic Organ Prolapse; Surgical Mesh; Pelvic Floor; chirurgické síťky; mechanické jevy; ženské pohlaví; stresová inkontinence moči; Humans; pevnost v tahu; mechanical failure; prolaps pánevních orgánů; Urinary Incontinence, Stress; Female; testování materiálů; Materials Testing; lidé